G423 Service evaluation of the management of osteoarticular infection over 8 years in a single centre. (27th April 2015) - Costa, A Rodrigues Da; Oguti, B; Ashby, A; Smith, A; Lim, E; Alexander, E; Fidler, K
Abstract : Aims: There is no national consensus on the management of osteoarticular infection (OAI). Practice varies widely throughout the United Kingdom, with differences in duration of antibiotic treatment, switching from intravenous (IV) to oral antibiotics and requirement for peripherally inserted central venous catheters (PICC). Data about recurrence and complication rates is scant. We aimed to evaluate local practice: analyse demographic data, antibiotic course duration and administration route, use of invasive lines and associated complications with a view to guideline development. Methods: OAI in children aged 0–17 years, presenting to one centre, from 01/09/2006–01/09/2014, identified through hospital coding, clinician and microbiology records. Results: Demographic Data 82 confirmed OAI cases: 55% male, 45% female, mean age 4.8 years. Preliminary data from the first 24 cases revealed none had significant co–morbidities, sickle cell disease or immuno–suppression. Pathogenesis Tibia most commonly affected site, followed by femur. Organisms isolated in under half the cases. 2 cases of severe PVL-MSSA disease identified Management Median duration of antibiotic course (IV and Oral) was 45 (range 7–358) days. Median duration of IV antibiotic course was 20 (range 6–75) days. Oral switch occurred in 76%, after a median of 18 (range 3–17 days) of IV antibiotics. Most had PICC lines inserted, complications included line sepsis (x1). Complication of OAI included hyperesthesia, and prolonged chronic OAI Conclusions: The first 24/82 cases analysed confirm wide variation in management, partly due to the diversity in age, presentation and organism. This highlights the difficulties for guideline development for this heterogeneous group. Full analysis will be presented at the conference. It will provide a comprehensive picture of current local practice, and add to national data being collected as part of the DINOSAUR study, to further understanding of this serious condition.